Regression of Discovery Learning Model and PBL Perspective Realistic Mathematics Education (RME) in Algebraic Materials - Diana Tri Purnamasari; Riyadi Riyadi; Sri Subanti (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The benefit of this research is to overcome student learning problems in algebraic material. The low learning achievement of students with the average national exam is low below the minimum completeness of graduation, this is influenced by one factor, namely conventional learning models or methods that do not support mathematics learning. Based on this, an alternative learning model is needed that can provide an understanding of student achievement abilities. In this case the Model of Discovery Learning and PBL with the Realistic Mathematics Education (RME) perspective. This study aims to determine the Regression Model of Discovery Learning and PBL from the Realistic Mathematics Education (RME) Perspective on Algebraic Materials. This study was conducted in Surakarta Junior High School with the subject of class VIII students. This type of research is an experiment with a 3x3 factorial design with a random sampling technique, each of which is taught using the discovery model and PBL perspective Realistic Mathematics Education (RME). The data was collected using a test, while the data analysis technique used inferential analysis of two-way ANOVA through prerequisite, balance, hypothesis, and further tests. The conclusion is that the problem-based learning model is better than discovery learning and direct learning. Problem-based learning Students who have low, medium, and high initial abilities who are treated with the Problem Based Learning model with the Realistic Mathematics Education approach have better mathematics learning achievements than the Discovery Learning model and the direct learning model. Students who have moderate initial abilities who are treated with the Problem Based Learning model with a Realistic Mathematics Education approach have better mathematics learning achievements than the Discovery Learning model and direct learning model, while students who receive the Discovery Learning model treatment have the same mathematics learning achievement with a direct learning model on the material of a two-variable linear equation system.